2018
DOI: 10.1007/s00216-018-1079-6
|View full text |Cite
|
Sign up to set email alerts
|

Selective detection of copper ion in complex real samples based on nitrogen-doped carbon quantum dots

Abstract: Highly selective nitrogen-doped carbon quantum dots (ND-CQDs) for copper ion (Cu) determination were synthesized by a solvent-free pyrolysis of citric acid and histidine. The resultant ND-CQDs display a stable bright blue fluorescence with a satisfactory product yield of 56% and quantum yield of 16%. The ND-CQDs not only show good photostability under continuous UV irradiation, but are also dramatically stable against extreme ionic strengths. The solid powders of the ND-CQDs re-dispersed in water still maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 36 publications
0
19
2
Order By: Relevance
“…Compared to the previous studies in the literature, the reported uorescence of CQDs decorated with S-and/or N-was sensitive to Cu 2+ and Fe 3+ ions, 79,80 while in the current work, the prepared CQDs decorated with hydroxyl groups are sensitive to Zn 2+ and Hg 2+ . The difference in sensitivity of the uorescence for CQDs against metal ions was attributed to the decorative groups 81 and consequently due to the interaction of Zn 2+ and Hg + ions with hydroxyl groups as the surface decorative groups of the applied CQDs.…”
Section: Fluorescence Detection Of Zn 2+ and Hg 2+contrasting
confidence: 73%
“…Compared to the previous studies in the literature, the reported uorescence of CQDs decorated with S-and/or N-was sensitive to Cu 2+ and Fe 3+ ions, 79,80 while in the current work, the prepared CQDs decorated with hydroxyl groups are sensitive to Zn 2+ and Hg 2+ . The difference in sensitivity of the uorescence for CQDs against metal ions was attributed to the decorative groups 81 and consequently due to the interaction of Zn 2+ and Hg + ions with hydroxyl groups as the surface decorative groups of the applied CQDs.…”
Section: Fluorescence Detection Of Zn 2+ and Hg 2+contrasting
confidence: 73%
“…Although the above‐mentioned methods have high selectivity, they often require tedious operation and expensive instruments. [ 95 ] The detection mechanism of heavy metals is based on the fact that interaction of such metals with nano sensors lead to quenching or enhancing of the fluorescence spectra, up to an excitation of 340 nm. Such effect involves the different sensing mechanisms mentioned in the Introduction.…”
Section: Cqds As Nano Sensors For Food Quality and Safetymentioning
confidence: 99%
“…[ 95 ] synthesized CQDs using citric acid as a carbon source and performed a test to determine the presence of Cu 2+ in fruit juice. [ 95 ] The dectection mechanism identified was charge transfer with dynamic quenching that resulted in the interaction between Cu 2+ and the nitrogen groups on the CQDs surface. Some reviewed LOD for Cu 2+ using CQDs nano sensors were 5, 10, and 190 nM.…”
Section: Cqds As Nano Sensors For Food Quality and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…4 Table S2 † lists the linear ranges and the LODs of different nanomaterial based probes toward the quantitation of Cu 2+ ions, showing that a lower LOD is provided by the I-C dots than that by the rest. [53][54][55][56][57][58][59][60] In addition, organic solvent is not required when applying this simple assay. Having high selectivity and a low LOD, the I-C dot probe holds great potential for the quantication of Cu 2+ ions in real samples containing complex matrixes.…”
Section: Sensitivity and Selectivitymentioning
confidence: 99%